A basic guide to eschatology making sense of the millennium - Erickson, Millard John, 1932- (Grand Rapids, MI Baker, 1998)
Includes bibliographical references and index.
Originally published 1977 as "Contemporary options in eschatology : a study of the millenium", which see also.
Keywords: Eschatology -- introductions